2010
DOI: 10.2174/1874079001003010055
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Breast Cancer

Abstract: MicroRNAs are a class of small non-coding RNAs that are involved in the negative regulation of gene expression primarily through binding to the 3'untranslated region of their target mRNA. MicroRNAs have multiple mRNA targets, each of which can be regulated by multiple microRNAs making this a complex regulatory network. The identification of their importance in different types of cancer and validation of their role in many processes related to cancer progression led to their description as a novel class of onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Our results were in agreement with other prior studies which reported that miR-21 over-expression was associated with tumor grades, higher proliferation index, and lymph node metastasis in BC [5,13,30,76]. Other previous studies showed that miR-21 levels are positively correlated with vascular invasion, visceral metastasis, and advanced clinical stage [13,46,77], and associated with poor response to therapy, and worse survival in BC [49,[78][79][80][81]. Moreover, miR-21 deregulation represented a global cancer phenomenon; associated with poor prognosis and survival in other cancer types including lung cancer [42,82], colorectal carcinoma [54,83], gastric cancer [84], pancreatic cancer [33], diffuse large B-cell lymphoma [36,37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were in agreement with other prior studies which reported that miR-21 over-expression was associated with tumor grades, higher proliferation index, and lymph node metastasis in BC [5,13,30,76]. Other previous studies showed that miR-21 levels are positively correlated with vascular invasion, visceral metastasis, and advanced clinical stage [13,46,77], and associated with poor response to therapy, and worse survival in BC [49,[78][79][80][81]. Moreover, miR-21 deregulation represented a global cancer phenomenon; associated with poor prognosis and survival in other cancer types including lung cancer [42,82], colorectal carcinoma [54,83], gastric cancer [84], pancreatic cancer [33], diffuse large B-cell lymphoma [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…status in BC cells, and demonstrated that miR-21 expression is induced by HER2 ? signaling via the mitogen-activated protein kinase (MAPK) pathway [70,77,85]. Another proposed mechanism for this association can be through the linkage of HER2 and miR-21 by chromosomal region amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Blenkiron et al [ 28 ] have previously observed higher expression of miR-145 in luminal-A samples, and miR-145 may be one of the miRNAs related to the breast cancer subtype. In addition, the identified let-7e for the basal-like gain group and miR-21 for the basal-like loss group are all approved to be breast cancer subtype related [ 29 , 30 ]. Furthermore, we used the Cyclus3D algorithm to identify the network motifs that are patterns of subgraphs that recur at frequencies much higher than those found in randomized networks (see Figures 2(a2) – 2(d2) ).…”
Section: Resultsmentioning
confidence: 99%
“…Depending on their targets, miRNAs can function as oncogenes or tumor suppressor genes in different cancers (1). Increasing research has suggested that aberrant expression/functions of miRNAs are associated with the progression of cancer and may serve as novel biomarkers for diagnosis and prognosis in cancers, and may be potential novel therapeutic agents for tumor suppression (25). miRNAs are involved in the regulation of cellular functions, including cell proliferation and apoptosis (6).…”
Section: Introductionmentioning
confidence: 99%